2018
DOI: 10.1159/000492578
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound with Bronchoscope-Guided Fine Needle Aspiration for the Diagnosis of Paraesophageally Located Lung Lesions

Abstract: Background: Diagnosing centrally located lung tumors without endobronchial abnormalities and not located near the major airways is a diagnostic challenge. Tumors near or adjacent to the esophagus can be aspirated and detected with esophageal ultrasound (EUS) using gastrointestinal endoscopes. Objective: To assess the feasibility and diagnostic yield of endoscopic ultrasound with bronchoscope-guided fine needle aspiration (EUS-B-FNA) in paraesophageally located lung tumors and its added value to bronchoscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 24 publications
1
30
0
1
Order By: Relevance
“…Another advantage of EUS‐B is that it provides access for evaluation of mediastinal lesions adjacent to the oesophagus. Novel usage of EUS‐B for the diagnosis of centrally located intrapulmonary lesions has been described . Two studies employing EUS‐B demonstrated a similar diagnostic yield of approximately 90% sensitivity and were comparable to conventional EUS for the diagnosis of intrapulmonary tumours; there were no reported complications .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Another advantage of EUS‐B is that it provides access for evaluation of mediastinal lesions adjacent to the oesophagus. Novel usage of EUS‐B for the diagnosis of centrally located intrapulmonary lesions has been described . Two studies employing EUS‐B demonstrated a similar diagnostic yield of approximately 90% sensitivity and were comparable to conventional EUS for the diagnosis of intrapulmonary tumours; there were no reported complications .…”
Section: Discussionmentioning
confidence: 97%
“…Novel usage of EUS‐B for the diagnosis of centrally located intrapulmonary lesions has been described . Two studies employing EUS‐B demonstrated a similar diagnostic yield of approximately 90% sensitivity and were comparable to conventional EUS for the diagnosis of intrapulmonary tumours; there were no reported complications . A notable finding was that 45% of cases were diagnosed using only the transoesophageal approach with EUS‐B .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Transthoracic sampling from lung lesions is performed guided by Ultra Sound (US), fluoroscopy or CT, and percutaneous non-lung lesions (e.g. peripheral lymph nodes, liver, spleen, skin) are reached by US-guided biopsy [5][6][7][8]. Whenever possible, histological biopsies were obtained (e.g.…”
Section: Biopsy Proceduresmentioning
confidence: 99%
“…There are very few studies including patients with previous non-diagnostic bronchoscopy that underwent EUS-FNA addressed to paraesophageal lung tumors [9,10] and few lung EUS-FNA studies included patients having either a negative bronchoscopy or a negative CT-guided biopsy [13][14][15][16]. A recent study supports the added value of EUS-FNA after a non-diagnostic bronchoscopy, showing an increase of the diagnostic yield from 51 to 91% [17].…”
Section: Introductionmentioning
confidence: 99%